Comparison of short‐ and long‐term effectiveness between ustekinumab and vedolizumab in patients with Crohn's disease refractory to anti‐tumour necrosis factor therapy. Issue 12 (28th April 2021) - Manlay, Luc; Boschetti, Gilles; Pereira, Bruno; Flourié, Bernard; Dapoigny, Michel; Reymond, Maud; Sollelis, Elisa; Gay, Claire; Boube, Mathilde; Buisson, Anthony; Nancey, Stéphane
Summary: Background: The best option between vedolizumab and ustekinumab after anti‐tumour necrosis factor (TNF) failure remains unclear in Crohn's disease. Aims: To compare the short‐ and long‐term effectiveness of vedolizumab and ustekinumab in Crohn's disease patients with prior anti‐TNF exposure. Methods: All Crohn's disease patients treated with ustekinumab or vedolizumab after exposure to at least one anti‐TNF agent were included from two referral centres. Primary endpoint was corticosteroid‐free clinical remission defined as Crohn's disease activity index <150 at week 54. Deep remission (corticosteroid‐free clinical remission and faecal calprotectin <100 µg/g) was assessed at week 14. Propensity‐matched analyses were applied to make the two groups comparable. Results: Overall, 312 patients (ustekinumab = 224 and vedolizumab = 88) were included. After propensity score analysis, ustekinumab was more effective to achieve corticosteroid‐free clinical remission at week 54 (49.3% vs 41.2%, P = 0.04) and deep remission at Week 14 (25.9% vs 3.8%, P = 0.02) than vedolizumab. The rate of primary nonresponders (6.7% vs 14.8%, P = 0.034) and the long‐term risk of drug discontinuation due to therapeutic failure (HR = 1.53 [1.04‐2.07], P = 0.029) were lower in patients treated with ustekinumab compared with vedolizumab. Predictors of ustekinumab failure were complicated phenotype (odds ratio [OR] = 2.35 [1.31‐4.22]; P = 0.004) and anti‐TNF primary non‐response (OR = 2.55 [1.27‐5.12]; P = 0.008). We did not find any predictor of corticosteroid‐free clinical remission in patients treated with vedolizumab. Vedolizumab was less effective than ustekinumab in patients >35 years old (OR = 0.41 [0.19‐0.87]), with noncomplicated phenotype (OR=0.42 [0.18‐0.96]), no prior bowel resection (OR = 0.49 [0.24‐0.96]), and no steroids at baseline (OR=0.47 [0.23‐0.97]). Conclusion: Ustekinumab was more effective to achieve early and long‐term effectiveness than vedolizumab in Crohn's disease patients who previously failed response to anti‐TNF agents.